Evaluation of the potential of Mycobacterium smegmatis as vaccine Candidate against tuberculosis by in silico and in vivo studies - Nguyen Thi, Le Thuy; Maura, Reinier Borrero; Férnandez, Sonsire; Reyes, Giselle; Perez, José Luis; Reyes, Fátima; García, María de los Angeles; Fariñas, Midrey; Infante, Juan Francisco; Tirado, Yanely; Puig, Alina; Sierra, Gustavo; et al. (Finlay Ediciones, 2010)
In this study, we scanned multiple published databases of gene expression in vivo of M. tuberculosis at different phases of infection in animals and humans, to select 38 proteins that are highly expressed in the active, latent and reactivation phases. The selected proteins were predicted for T and B epitopes. For each proteins, the regions containing T and B epitopes were selected at the same time to look for identical epitopes on M. smegmatis based on sequence alignments. Preliminary studies of humoral immunogenicity and cross-reactivity with M. tuberculosis in mice using two M. smegmatis-derived experimental vaccines were carried out, demonstrating the immunogenicity of M. smegmatis proteoliposomes and the recognition of M. tuberculosis proteins by the sera of animals immunized with this vaccine candidate. The conjunction of in silico and in vivo studies suggested the potential for future evaluation of M. smegmatis as vaccine candidate against tuberculosis using different strategies